1, 2‐Dichlorobenzene Pretreatment via Phosphoric Acid‐Mediated Fenton Reagent. (1st July 2015) - Richmond, Mark D.
ABSTRACT: : A large industrial water resource recovery facility needed to significantly reduce the amount of 1, 2‐dichlorobenzene (ODCB) entering its biological treatment units. Numerous Advanced Oxidation Processes (AOPs) were considered based on literature and industry reports. Many AOPs appear to be incompatible with some of the native species present in groundwater or wastewater matrices. Iron, in particular, is often viewed as a nuisance increasing the complexity of the overall treatment scheme. The approach used in the current study was to incorporate the new AOP into the existing groundwater matrix and facilities as much as possible. To that end, native iron was exploited as the reaction catalyst, an acid was selected to fit with current macro nutrient needs of the biotreatment units, and the reactor was designed to require minimum modification of the existing facilities. The "green chemical" (Noyori, 2003 ) treatment process selected was demonstrated at full‐scale, achieving good agreement with the results of prior laboratory studies. Up to eighty percent destruction of ODCB was demonstrated in a new pretreatment unit whose effluent fit seamlessly with the existing bioreactors.